Pengaruh Work Life Balance, Kepemimpinan Transformasional, dan Lingkungan Kerja Nonfisik terhadap Kepuasan Kerja Pegawai - Irensiana Sama Bili; Anggraeny Paridy; Stanis Man; Apryanus Fallo (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This study examines how work-life balance, transformational leadership, and the non-physical work environment affect employee job satisfaction at the Statistics Indonesia Office of East Nusa Tenggara Province. A quantitative survey design was applied to all 98 employees using saturated sampling. Data were collected through questionnaires and interviews and analysed with descriptive statistics and multiple linear regression. The findings show that job satisfaction, work-life balance, and the non-physical work environment were in the good category, whereas transformational leadership was only fairly good. Partially, work-life balance and the non-physical work environment had positive and significant effects on job satisfaction. Transformational leadership showed a significant but negative effect. Simultaneously, the three variables significantly explained job satisfaction with a high coefficient of determination. These results highlight the importance of balanced work arrangements, supportive work relations, and more context-sensitive leadership practices. Keyword: job satisfaction; non-physical work environment; transformational leadership; work-life balance